Proton Magnetic Resonance Spectroscopy: relevance of glutamate and GABA to neuropsychology - Ende, Gabriele (Neuropsychology review, 2015)
Proton Magnetic Resonance Spectroscopy (MRS) has been widely used to study the healthy and diseased brain in vivo. The availability of whole body MR scanners with a field strength of 3 Tesla and above permit the quantification of many metabolites including the neurotransmitters glutamate (Glu) and γ-aminobutyric acid (GABA). The potential link between neurometabolites identified by MRS and cognition and behavior has been explored in numerous studies both in healthy subjects and in patient populations. Preliminary findings suggest direct or opposite associations between GABA or Glu with impulsivity, anxiety, and dexterity. This chapter is intended to provide an overview of basic principles of MRS and the literature reporting correlations between GABA or Glu and results of neuropsychological assessments.